Recensión: "La ciudad y sus miedos: la pasión restauradora" de Alicia Entel - Korstanje, Maximiliano (MAD, 2009)
Recensión del libro <!--[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->"La ciudad y sus miedos: la pasión restauradora" de Alicia Entel